Why Azerbaijani Learners are Less Proficient in Oral Communication after having 9 Years of English Language Instruction : Central versus Non-Central Schools in Baku - Suleymanova, Aytan (ADA University, 2022)
The current research aims at investigating the existing obstacles that lead to having reduced oral production competence of the English language among Azerbaijani learners. The researcher sets a goal of exploring the reasons why school graders cannot master oral production of English despite having 9 years of language instructions. With that in mind, a comparative analysis has been held with 4 schools located in Baku, Azerbaijan – 2 central and 2 non-central educational settings. A mixed-method has been applied with 80 students – 40 from central and 40 from non-central schools, 12 English language teachers, and 3 education specialists to dig into the roots of the existing issue. To gather needed data, testing students’ level of English-speaking skills, conducting surveys, holding interviews, and statistical analysis of findings have been adopted to get as much informative data as possible. Study findings revealed that factors of teacher quality, having grammar-focused lessons, lack of language environment, assessment tasks, and the student attitude towards mastering English language are the barriers in Azerbaijani students improving their communicative competencies of English. Moreover, all the mentioned factors, in fact, create the gaps between the students studying at central schools and the ones who study at non-central educational settings. Because the listed components are lacking in non-central schools, students studying there get little to no chance to develop their spoken English. To eliminate the obstacles, the provision of professional development trainings for teachers, reconsidering the lesson plans and syllabi to make English classes more communication based, and the integration of speaking tests to assessment system should be brought to the attention of faculty members and specialists of education.
Keywords: English Language -- Study and teaching -- Azerbaijan; Language and languages -- Study and teaching -- Azerbaijan; Education -- Research -- Azerbaijan; Education